Diagnostic and prognostic value of autoantibodies for diabetes mellitus. A novel T1D autoimmunity target - zinc transporter 8 (ZnT8) - Olga Sergeevna Shapoval'yants; Tatiana Vasil'evna Nikonova (Сахарный диабет)
The progressive loss of beta cells in Type 1 Diabetes (T1D) is a result of chronic autoimmune attack targeted at diverse molecules expressing in thepancreatic beta cells. The appearance of cellular and humoral autoimmunity precedes the clinical manifestation of T1D. There are several autoantigenswhich are supposed to be involved in pathogenesis of TD1. Zinc transporter 8 (ZnT8; Slc30A8) was identified as a novel T1D autoimmunitytarget.